Poetry for students. presenting analysis, context and criticism on commonly studied poetry Volume 39. - Constantakis, Sara; Kelly, David J.; Gale Group (Detroit, Mich. Gale, 2012)
Features discussion and analysis of poems of all time periods, nations, and cultures. Provides an overview of the poem and discussion of its principal themes, images, form and construction.
Corinna's going a-maying / by Robert Herrick -- Domestic violence / by Eavan Boland -- Exile / by Julia Alvarez -- Flounder / by Natasha Trethewey -- Frost at midnight / by Samuel Taylor Coleridge -- Ghost of a chance / by Adrienne Rich -- Let evening come / by Jane Kenyon -- The listeners / by Walter de la Mare -- Miracles / by Walt Whitman -- The powwow at the end of the world / by Sherman Alexie -- Sea canes / by Derek Walcott -- Seven laments for the war-dead / by Yehuda Amichai -- Song for the last act / by Louise Bogan -- Syrinx / by Amy Clampitt -- Thoughts of Hanoi / by Nguyen Thi Vinh -- The tide rises, the tide falls / by Henry Wadsworth Longfellow.
Description based on print version record.
Includes bibliographical references and indexes.
Electronic reproduction.
Keywords: Poetry -- Study and teaching; Poetry -- History and criticism; Poetry, Modern -- 19th century; Poetry, Modern -- 20th century; Poetry, Modern -- 21st century